The challenge of neuroimaging during pregnancy - Ghazal, Kariman Suel; Shatila, Abdul Rahman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Central nervous system conditions may affect every aspect of female reproduction from fertility to lactation. The objective of this study was to examine the performance of computed tomography and magnetic resonance imaging in the diagnosis of maternal neurologic disorders and to examine the outcome of pregnancies complicated by abnormal neurologic imaging. Methods: Retrospective observational study of 20 parturients presenting with severe neurologic symptoms (January 2006 to January 2016). Results: Abnormal neuro-radiological findings were found. Only 10% of the computed tomography-scans were normal. Both magnetic resonance imaging and computed tomography that were performed in all cases showed cerebral edema (90%) with different degrees, thereby cerebral edema was the predominant lesion. Pertaining to its localization, 65% were localized in the parietal or occipital area, 10% in the paraventricular area, and 10% were diffused. Also, 35% showed intracerebral hemorrhage and 10% showed cerebellar hemorrhage. The incidence of neurological disorders in pregnancy and puerperium was high. Epilepsy and headache were the most common primary and secondary neurological disorders. Conclusions: The role of neuroimaging in diagnosing neurological disorders is crucial for prevention of severe complications.